PEMBELAJARAN KONTEKSTUAL DALAM PENINGKATAN EFEKTIVITAS PEMBELAJARAN ANALISIS RANGKAIAN LISTRIK - Istiyono, Edi; Supahar, Supahar; Pujianto, Pujianto (LPPMP Universitas Negeri Yogyakarta, 2008)
The objectiveof research are: (1) to discover step of learning community; (2) todiscover acomputer based media and module thatsupport of learning community;and (3) to discover type of authentic assessment that support of learningcommunity that can raise effectively of learning of Circuit Analysis. Subject ofresearch is the student of the Study Program of Physics of Mathematics and ScienceFacultyin Yogyakarta State University that takes the Circuit Analysis Subject of 28students. To detetrr)ine daia of the research is used methods: (1) test, (2)observation, and (3) questioner. Test is used to detetrr)ine data of the learningachievement of the Circuit Analysis. Observationto determine of student activity.By analyzingof data, it is concluded that: (1) Steps of learning community thatcan raise effectively of learning of Circuit Analysis are: (a) Lecturer explains pointsof lecture,(b) Lecturer gives different tasks to each group, (c) class is divided to 3-4person/ group, and (d) each of group present their paper and another groupperceive; (2) Type of authentic assessment in contextual teaching and learning thatapply learningcommunity can rise effectively of learning of Circuit Analysis are:(a) activity,(b) task, (c) quiz, and (d) test; and (3) Media of learning and modulethat support to learning community to rise effectively of learning of CircuitAnalysis. Media construction is figure, simple explanation, color-animation font.Module constructionis complete theory, problem solving, and drill